SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84343-ms
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Fully Coupled Reservoir Simulation Approach for Deliverability and Cycle Enhancement in a Gas Storage Field

Abstract: Successful optimization of a gas storage field begins with proper reservoir description and evaluation of deliverability and storage capacity in the reservoir. Once true reservoir potential is determined, the effects of surface piping and surface-facility pressure constraints can be integrated to quantify a more accurate estimate of the actual deliverability, injectivity, and working gas capacity of the gas storage field. This paper discusses the integration of previously used deliverability enhancement method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…al. 12 presented a case history of a storage field design optimization with a numerical model where geologic modeling was integrated into a reservoir simulation package that incorporates modeling of subsurface, wellbore, and surface gathering system flows. They found that the fully coupled reservoir characterization study was successful in improving overall field operation efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…al. 12 presented a case history of a storage field design optimization with a numerical model where geologic modeling was integrated into a reservoir simulation package that incorporates modeling of subsurface, wellbore, and surface gathering system flows. They found that the fully coupled reservoir characterization study was successful in improving overall field operation efficiencies.…”
Section: Introductionmentioning
confidence: 99%